2017
DOI: 10.1039/c7ra00433h
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped porous activated carbon derived from cocoon silk as a highly efficient metal-free electrocatalyst for the oxygen reduction reaction

Abstract: Heteroatom-doped porous carbon has attracted considerable research interest due to its effective catalytic activity towards the oxygen reduction reaction (ORR). In this study, nitrogen-doped porous activated carbon (PAC) is fabricated via a facile heat-treatment and chemical activation of cocoon silk in an inert gas atmosphere. The prepared PAC exhibits excellent ORR catalytic performances with the half-wave potential of À0.13 V and an onset potential of +0.03 V vs. Ag/AgCl, which match the Pt/C catalyst and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Iwazaki et al presented silk‐derived activated carbon as a catalyst for the ORR in a PEM fuel cell . Fu et al indicated that the fiber structure of CS can be preserved via precarbonization and further activation with ZnCl 2 (at 800 °C) . Figure b 1 ,b 2 show the silk fiber before and after carbonization at 800 °C, respectively.…”
Section: Electrocatalysts From Zoomassmentioning
confidence: 99%
“…Iwazaki et al presented silk‐derived activated carbon as a catalyst for the ORR in a PEM fuel cell . Fu et al indicated that the fiber structure of CS can be preserved via precarbonization and further activation with ZnCl 2 (at 800 °C) . Figure b 1 ,b 2 show the silk fiber before and after carbonization at 800 °C, respectively.…”
Section: Electrocatalysts From Zoomassmentioning
confidence: 99%
“…However, this carbon typically obtained from HTC presents the spherical morphology with rather low surface areas and poor electron conductivity ,,. And direct pyrolysis of biomass usually results in the formation of irregular structures and lack of sufficient porosity ,. As a result, these primary biomass‐derived carbons are relatively sluggish as electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[50,51,54] And direct pyrolysis of biomass usually results in the formation of irregular structures and lack of sufficient porosity. [39,[55][56][57] As a result, these primary biomass-derived carbons are relatively sluggish as electrodes. Therefore, upgrading the quality of biomass-derived carbons and endowing them with potentially huge exposed field, hierarchically porous structure and effective nitrogendoping property are highly expected to achieve their specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…1b) displays three peaks positioned at 531.5, 533.3, and 535.4 eV, which correspond to C]O, C]O, and C-OH. 27,30 (b) Thermogravimetric analysis-TGA. TGA of jujube seeds (Fig.…”
Section: Resultsmentioning
confidence: 99%